Effect of Kangaroo Mother Care on Heart rate, Respiratory rate and Temperature in Low Birth Weight Babies - Pramila Verma; Vijay Verma (International Journal of Medical Research and Review, 2014)
Background: Kangaroo mother care (KMC) involves skin-to-skin positioning of the infant in an upright position against the mother’s chest. The two other components of KMC are frequent and exclusive breastfeeding (where possible) and early discharge from hospital. Aim of present study was to asses effect of kangaroo mother care on heart rate, respiration rate and temperature of low-birth weight preterm newborns admitted in a tertiary care centre of central India.Methods: Low birth weight babies (weighing< 2000 grams) were given kangaroo mother care (KMC) for 30minutes. Pre and post KMC heart rate, respiratory rate and temperature were measured.The evaluations were done once a day, for three consecutive days and the mean values were taken for analysis. The data was statistically analyzed using plus 6.0 statistical software. Student t test was used to find out the statistical difference between two mean SD.Results: Results of the study reveal that changes in heart rate and respiration rate after application of kangaroo care was insignificant (p>0.05) where as kangaroo care is highly effective in maintaining skin temperature (p<0.0005).Conclusion: KMC maintains heart rate, respiratory rate and temperature in a stable preterm low birth weight babies.